Revision of the horseface loaches (Cobitidae, Acantopsis), with descriptions of three new species from Southeast Asia - David A. Boyd (2018)
Copyright © 2017 Magnolia Press. Acantopsis (Cobitidae) is revised based on analysis of morphological and molecular data. Four of the six available names, A. dialuzona, A. spectabilis, A. octoactinotos, and A.Thiemmedhi, are valid, and three new species, A. rungthipae, A. dine-ma, and A. ioa, are described. All species are described morphologically, distributions are mapped, and relationships are discussed for those for which molecular data (CO1, RAG1) are available. Labial barbels, color pattern, and meristic counts are the most diagnostic features. Although the long snout of Acantopsis is perhaps the most emblematic attribute of the genus, its relative length increases with growth, reducing its taxonomic value. Species can be difficult to identify on the basis of color pattern alone, as habitat and preservation methods appear to strongly influence the color pattern. Despite interspecific overlap of some highly variable traits, each species has a unique set of morphological characteristics that re-main observable even when the color pattern is obscured, and some species are restricted to single drainages, greatly sim-plifying identification. The phylogenetic analyses revealed high molecular divergen ce between even the most morphologically similar species, with mean uncorrected CO1 p-distances between species ranging from 12.1-15.4%. Spe-cies of Acantopsis exhibit significant genetic structuring consistent with recognized freshwater ecoregions. Acanthopsis lachnostoma Rutter 1897, from Swatow, China, is not assignable to Acantopsis.